BUDAYA BACA SISWA SMP DI ERA INTERNET - Nurhadi . (Fakultas Sastra Universitas Negeri Malang, 2011)
The Internet is believed to have changed reading habits: deep reading has shifted due to the easy access on the Net. This research is intended to unravel the reading behavior of Junior High School students in the Municipality of Malang. The results indicate that reading is not listed as a favorite past-time: they spend a little time reading. The trend is that they tend to spend their time for accessing the Internet in a way different from that of the previous time. The analysis shows that there is a positive correlation between reading habit and reading variables related to the Internet.